Pengaruh Mekanisme GCG, Kinerja Keuangan, dan Umur Perusahaan terhadap Pengungkapan Sustainability Report - Akhmad Faizhal; Ratna Anggraini; Muhammad Yusuf (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study aims to analyze the influence of independent commissioners, audit committees, profitability, and firm age on sustainability report disclosure. This study uses a quantitative method with energy sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period as the analysis unit. The data in this study uses secondary data taken from financial reports and sustainability reports obtained through the IDX website and the company's official website. The sample was selected using purposive sampling with a final number of observations of 163. This study uses panel data regression to investigate the relationship between independent variables and sustainability report disclosure using Eviews 13 software. The study’s findings demonstrates that independent commissioners and audit committees have no significant effect on sustainability report disclosure. Furthermore, profitability has a significant negative effect on sustainability report disclosure. In the meanwhile, firm age has a positive effect on sustainability report disclosure.